Level of literacy and clinical outcomes in patients with Chagas disease: SaMi-Trop project. (30th September 2020) - Quintino, N; David, G; Sabino, E; Silva, J L; Ribeiro, A L; Ferreira, A; Oliveira, L; Oliveira, C; Cardoso, C
Abstract: Background: Chagas disease (CD) is a neglected tropical disease that affects mainly vulnerable population, whose majority has low ability to understand health information. This study aimed to assess the prevalence of health literacy (HL) and its association with sociodemographic, quality of life, health care aspects and worse clinical outcomes. Methods: This is a cross-sectional study developed inside a cohort study (SaMi-Trop) including 1959 patients. It has been conducted in an endemic region to CD in Brazil. The eligible criteria for HL evaluation was the ability to read. The HL was assessed with SALPHA-18 scale and literacy was categorized in inadequate HL; adequate HL and; illiterate. Multiple models were adjusted using binary logistic regression, multinomial and beta regression models using the gamlss framework. Results: Of the patients included, 1136 (74.1%) are illiterate. For HL assessment, only 397 managed to complete the HL evaluation. The prevalence of inadequate HL was 85.1% (338), only 59 patients (14.9%) had adequate HL. Our results are as following: 1) being illiterate increases the chance of using more drugs when compared to individuals with adequate HL - 1 or 2 drugs (OR: 1.96; CI: 1.06-3.62) and 3 to 4 medications (OR: 3.06; CI:1.44-6.52), to have hypertension (OR: 2.24; CI: 1.29-3.90), report an average self-perceived health (OR: 2.97; IC: 1.63-5.42) and report poor self-perceived health (OR: 3.67; CI: 1.71-7.89); 2) inadequate literacy increases the chance of using 3 to 4 medications (OR: 2.26; CI: 1.04-4.93) and report an average self-perceived health (OR: 2.48; CI: 1.34-4.62); 3) Illiterate patients present worst quality of life scores in Physical (OR: 0, 730; CI: 0, 583-0, 914), Psychological (OR: 0, 671; CI: 0, 544-0, 828) and Environmental (OR: 0, 727; CI: 0, 601-0, 880) domains. Conclusions: We found a high prevalence of inadequate HL; it was associated with worse clinical outcomes and poor self-perceived health. Key messages: Our findings reinforce the importance of improving health communication in CD patients seeking to avoid unfavorable outcomes. A high prevalence of inadequate health literacy was observed in our study, which can impact the self-care ability of patients with CD.